PENGARUH “JOKOWI EFFECT” TERHADAP HARGA SAHAM - - Amirah (Universitas Muhammadiyah Semarang, 2015)
The purpose of this study is to examine the effect of “Jokowi Effect” to abnormal stock return of companies included LQ 45 during the 30 days before and 30 days after the inauguration of Joko Widodo become President of the Republic of Indonesia. samples were selected by using purposive sampling method with the criteria included in the LQ 45 index over the study period , as well as havingstock price data that can be accessed through Yahoo finance, in this case 32 shares selected into thesample. By using the event study approach, the results of different test paired sample t tests showedthat the value of T test of -1.146 < 1.96 with a significance level of 0.261 > 0.05, which means that H0is accepted, that there was no significant difference between the company's stock price LQ 45 at thetime before and after the inauguration of Joko Widodo as the President of the Republic of Indonesia. Keywords: Jokowi Effect, LQ 45, Abnormal Return